FAKTOR-FAKTOR YANG MEMPENGARUHI KETEPATAN WAKTU PELAPORAN KEUANGAN DANA ZAKAT PADA BAITUL MAL KOTA LHOKSEUMAWE - Hikalmi, Hikalmi; Alfahmi, M. Lutfi; Oktarina, Maulia; Andirfa, Mulia (Accounting Departement Economics and Business Faculty Syiah Kuala University, 2022)
This study aims to examine the effect of the influence of the quality of human resources, internal control systems and utilization of information technology on the timely reporting of zakat funds in Baitul Mal Kota Lhokseumawe. The data used in this study were primary data by distributing questionnaires to 32 employees in Baitul Mal Kota Lhokseumawe which were used as research samples. Data processing is performed with the help of multiple linear regression equation models. The results showed that: Partially the quality of human resources, internal control systems and utilization of information technology have a significant effect on the timeliness of financial reporting of zakat funds in Baitul Mal Kota Lhokseumawe. Simultaneously the quality of human resources, internal control systems and the use of information technology have a significant effect on the timeliness of financial reporting of zakat funds in Baitul Mal Kota Lhokseumawe. The quality of human resources, internal control systems and utilization of information technology can explain their effects on the timeliness of financial reporting of zakat funds in Baitul Mal Kota Lhokseumawe by 72.6%. The remaining 27.9% is influenced by other variables outside this research model such as understanding accounting, supporting tools, organizational commitment, and others.